What the golden rule teaches us about ethics. - Ward, Shane William (Philosophy & Phenomenological Research, 2025)
The Golden Rule is regularly used in ordinary life, across many different cultures, to acquire new moral knowledge. At the same time, the Golden Rule is widely ignored both in ethics and metaethics because it seems to be an implausible normative theory. Most philosophers who have paid it any attention have thought that, at best, it is an initially tempting thought whose appeal should be explained by the ultimately correct normative theory. My aim in this paper is to attend to an alternative possibility: the Golden Rule teaches us something about metaethics, in the form of moral epistemology, rather than normative ethics. I will argue that sentimentalism, the view that the emotions are an essential source of moral knowledge, provides a compelling explanation of the usefulness of the Golden Rule. Before giving the sentimentalist explanation, I explain why proposed alternative sources of moral knowledge provide less compelling explanations of its usefulness.